Sound Governance Analysis in the Innovation of Traditional Market Revitalization and Street Vendors Management - Holidin, Defny; Handini, Rilyan Shela (UI Scholars Hub, 2014)
Departed from the innovative programs during the period of Joko Widodo in Surakarta that are still made as the model of the local public service reform, this article aims to discover and analyze the innovations of the Municipal Government of Surakarta (as known as Solo), the revitalization of the traditional market and the management of the street vendors, under the leadership of Joko Widodo (known also as Jokowi) as the mayor (2005 – 2012) by using to Sound Governance Model. The research uses positivist approach through several data collection techniques, such as, in-depth interview with the program performing actors in the local government and the beneficiary actors; observation; and literature review. The data was collected throughout 2012 – 2013 after Joko Widodo is no longer the incumbent Mayor, in order that the information of the innovations sustainability can be noticed. The outcome was analyzed as univariate and descriptively towards the dimensions of Sound Governance Model. The study suggests that there is a novel approach in running the innovative program of the traditional market revitalization and the street vendors management through an adaptive environmental development without discarding the orientation toward society-empowerment in Surakarta. Even so, the manifestation of the sound governance has not been related to the refinement of the positive impact for the stakeholders like traders, due to lack grounded from their substantive needs, poor performance management, and also the lacking stakeholder engagement in the program monitoring and evaluation. In contrast to previous existing reports, this research also suggests that the coherence between leadership and administrative capacity is inevitable for the sustainability of the innovation practices.